The Role of Peer Tutoring in Enhancing Students' Conceptual Understanding in Social Studies: A Qualitative Study at SMPN 2 Larangan - Atiqoh Saadatul Qorina Atiqoh (SOCIALE: Jurnal Internasional Kajian Sosial, 2026)
Social Studies (IPS) learning at the junior high school level still faces the problem of low students' conceptual understanding, which is indicated by students' lack of ability to relate the material to real-life contexts. One alternative learning strategy that can be used to overcome this problem is the implementation of peer tutoring. This study aims to describe the role of peer tutors in improving IPS conceptual understanding in students of class VIII-D at SMP Negeri 2 Larangan. This research uses a qualitative approach with a descriptive type. The research informants numbered eight people, consisting of IPS subject teachers, students who acted as peer tutors, and students participating in peer tutoring activities. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis uses an interactive model that includes data reduction, data presentation, and verification or drawing conclusions. The research results show that peer tutors contribute to improving students' conceptual understanding, particularly in the indicators of the ability to provide examples and compare social phenomena. More egalitarian learning interactions encourage active student participation and help the process of knowledge construction through discussion and collaboration. Nevertheless, the effectiveness of peer tutors is influenced by the tutor selection system and the duration of activity implementation. Therefore, the development of a more systematic and sustainable peer tutor model is needed to support the improvement of social studies learning quality.